Integrated management of development in Functional Urban Areas. The case of metropolitan areas in Slovenia - Danielewicz, Justyna (Rozwój Regionalny i Polityka Regionalna, 2024)
Metropolisation and globalisation have had a significant influence on space and development, both in terms of the physical and social aspects of the environment. Metropolitan areas have become engines of development, centres of economic activity, innovation, and culture, attracting people and businesses from all over the world. However, this concentration of people and activities has also resulted in significant challenges concerning management of their sustainable development. Most of today’s challenges are spread across administrative borders and working at the level of the metropolitan area can help develop innovative solutions that benefit the wider functional urban areas. Many of the problems faced by territories cut across sectors and effective solutions require an integrated approach to managing the development of functional urban areas (FUAs) and cooperation between the various authorities and stakeholders involved. The aim of this study is to evaluate the degree to which an integrated approach to development management is used in the management of metropolitan areas in Slovenia. The research focuses on FUAs of Ljubljana and Maribor. The results show that policy makers understand the need for integrated planning and management on a supralocal level. Local authorities commonly cooperate with each other using legitimate forms of institutionalising inter-municipal cooperation.